ANALISIS KETERKAITAN FUNGSIONAL WILAYAH DAN SEKTORAL PERBATASAN JAWA TENGAH JAWA TIMUR DAN IMPLEMENTASINYA DALAM KERJASAMA PENGEMBANGAN WILAYAH - Mursid Zuhri (Badan Perencanaan Pembangunan, Penelitian dan Pengembangan Daerah Provinsi Jawa Tengah, 2013)
Incomplete understanding of regional autonomy local governments often have misperceptions of understanding of the implementation of regional autonomy. Sectoral and regional ego ego often be quite disturbing in the implementation of regional autonomy. Conditions that will undoubtedly lead to inefficiency and lack of local government pegelolaan serasian relations among local governments. Sectoral issues, externalities autonomous region, inter-regional interdependence function and hierarchy of public goods is a fundamental problem underlying the need for regional development and sectoral cooperation. Cooperation among local governments (counties / cities) in one province / provinces should be encouraged thing. The success and achievements of the cooperation is dependent upon the ability of the district / city level organizing cooperation in local development. Nevertheless, the role of the private and the public must also be examined and optimized. In line with the concept of good governance, networks of cooperation among these three actors will largely determine the quality / success of the implementation of regional autonomy of studies in the area Ratubangnegoro (Blora, Tuban, Apex and Bojonegoro), and the presence of a significant role in encouraging private sector co-operation supporting other business sectors. While in the case of cooperation in Pawonsari (Pacitan, Winton and Wonosari / Gunungkidul) occurs patterns that emerged from the realization of cooperation with local governments to improve the welfare of its people are relatively the highest compared to other areas. The issue of public services and the use of natural resources with a central area of ​​cooperation. Some problems were found in this study on the implementation of the cooperation between the district / city is still the presence of differences in interest and priority areas / sectors cooperated, there are still large dependence on the central government, budgeting issues, and the legality of the law as an umbrella partnership. Therefore, things that need to be considered to sustain efekktivitas and sustainability of cooperation between districts / cities are forming a strong partnership base. District / city government needs to monitor the potential, constraints and sectoral and regional cooperation. Furthermore, the results of such monitoring are classified in the published schemes for target groups to strengthen and improve the knowledge of stakeholders on the importance of such cooperation.